You are on page 1of 5

# CY1202

AY2013/2014
SOLUTION SET 2
(Q1) (i) The inversions of are
(1, 2), (1, 3), (1, 5), (1, 6), (2, 3), (2, 6), (4, 5), (4, 6).
Thus N () = 8 and sgn() = (1)N () = 1.
(ii) See Example 2.4.




1 2 3
1 2 3
1 =
,
2 =
,
1 2 3
1 3 2




1 2 3
1 2 3
4 =
,
5 =
,
2 3 1
3 1 2


3 =

6 =

1 2 3
2 1 3

1 2 3
3 2 1

,
.

## (iii) Use the notation in part (ii),

det(A) = sgn(1 )A1,1 (1) A2,1 (2) A3,1 (3) + sgn(2 )A1,2 (1) A2,2 (2) A3,2 (3) +
+ sgn(6 )A1,6 (1) A2,6 (2) A3,6 (3)
=A1,1 A2,2 A3,3 A1,1 A2,3 A3,2 A1,2 A2,1 A3,3 + A1,2 A2,3 A3,1 + A1,3 A2,1 A3,2 A1,3 A2,2 A3,1
=aei af h bdi + bf g + cdh ceg.
(Q2) (i) It is just a routine application of elementary row operations.

2 1 0 E3,2 ( 1 ) 2 1
0
2 1 0 E3,1 ( 1 ) 2 1 0
E2,1 (1)
2
8
A = 2 5 2 2 5 2 0 4 2 0 4 2 = A0
1 1 0
0 21 0
0 21 0
0
0 14
Applying Exercise 2.10 (i) and 2.13 (ii) gives us


 
 
1
1
0
det (E2,1 (1)) det E3,1
det(A) = det(A).
2 = det(A ) = det E3,2
8
2
(ii) We may, first, do
in part (i) to get

2 1 0
2 5 2

B=
1 1 0
0
0 0
0
0 0

## the same elementary row operations to the first three rows of B as

2 1
0

0
4
2

E3,2 ( 18 )E2,1 (1)E3,1 ( 12 )

0
0 14
0
2 1
0
0
1 1
0
0
0

2 1
0

0
4
2

E5,4 ( 21 )
0

0 14
0
=B
0
0
0 2 1
0
0
0 0 32
1

2 1
1 1

## Similar to part (i), we have


 

 

 
1
1
1
6 = det(B ) = det E5,4
det E3,2
det (E2,1 (1)) det E3,1
det(B) = det(B).
2
8
2
0

A1 . . .
0 A2

A=
.
.
..
..
0 0 Ak

## then det(A) = det(A1 ) det(A2 ) det(Ak ).

(iii) Same as part (i) and (ii), it is left to you.
(Q3) We may either use the multi-linear property of determinant or definition. By multi-linear
property, in each step, you factor out the constant factor r from a particular row and there
are n rows of them. By definition, (rA)ij = rAij ,
det(rA) =

Sn

Sn

= rn

## sgn()a1,(1) a2,(2) an,(n)

Sn

= rn det(A).
(Q4) The easiest example I can probably think of is

A=

1 0
0 0


, B=

0 0
0 1


.

(Q5) For this question, you have to know what a reduced row echelon form is. Since everyone
knows row operations pretty well, I will combine some operations together.

1
2 1 0
1 2 1 0
1 0 5 6
E2,1 (1)E3,2 (1)
E3,2 (1)E1,3 (1)
A = 1 0 3 5 0 2 4 5 0 2 4 5
1 2 1 1
0 2 4 6
0 0 8 11

1 0 5
T3 (1/8)T2 (1/2)

0 1 2
0 0 1

1 0 0 87
5 E1,3 (1)E2,3 (1)
0 1 0 41 = R.
2
11
0 0 1 11
8
8
6

The matrix E is the product of the elementary matrices involved above (yes, it is tedious...).

## (Q6) We show that ((AB)> )ij = (B > A> )ij .

((AB)> )ij = (AB)ji
m
X
=
Ajk Bki
=

k=1
m
X

>
A>
kj Bik

k=1

m
X

> >
Bik
Akj

k=1
>

= (B A> )ij .
(AB Y Z)> = ((AB Y )Z)> = Z > (AB Y )> = = Z > Y > B > A> .
(Q7) (i) Since BB 1 = In , we have 1 = det(In ) = det(BB 1 ) = det(B) det(B 1 ). Thus
det(B 1 ) = det(B)1 .
(ii) Use Question 6 to get
In = In> = (BB 1 )> = (B 1 )> B > .
This show that (B 1 )> is the inverse of B > ; namely (B > )1 = (B 1 )> .
(iii) Use part (i).
det(BAB 1 ) = det(B) det(A) det(B 1 ) = det(B) det(A) det(B)1 = det(A),
det(ZY BAB 1 Y 1 Z 1 ) = det(Z(Y BAB 1 Y 1 )Z 1 )
= det(Y BAB 1 Y 1 )
..
.
= det(A).
(Q8) This is a routine exercise. We only compute adj(A) and A1 . Let us make sure that A is
invertible by showing that det(A) 6= 0. Using Laplace expansion of the determinant of A
along third column, we have


2 1
(2,3)
2+3
det(A) = 2 A
= 2(1) det
= 2 6= 0.
1 1
Recall that A(i,j) = (1)i+j Mij and adj(A)ij = A(j,i) . For instance,


1 0
(2,1)
2+1
= (1) det
= 0,
1 0


1 0
(3,1)
3+1
= (1) det
= 2.
5 2
Once you have obtained the adjugate matrix adj(A) of A. Then, since det(A) 6= 0, we have

1 0 1
2 0 2
1
1
2 0 4 = 1 0 2 .
A1 =
det(A)
2 3 1 8
3 1 4
2

## (2.5) The inversions are

(1, 2), (1, 4), (1, 5), (2, 4), (3, 4), (3, 5), (3, 6).
Thus N () = 7 and sgn() = 1.
(2.10 (i)) Ea,b (r) and Ta (r) are triangular matrices. Thus det(Ea,b (r)) = 1 and det(Ta (r)) = r. The
determinant of Sa,b is 1.
(2.13) (i) The fact that det(Sa,b ) = 1 is because after swapping the ath and bth row of Sa,b we
obtain the identity matrix. According to the skew-symmetric property, we have


a b
det(Sa,b ) = sgn
det(In ) = (1)1 1 = 1.
b a
(ii)

R1
R1
.

.
..

.
.

det(Ea,b (r)A) = det Ra + r Rb = det Ra + r det Rb = det(A) + r 0 = det(A)

.
.
..

..
..
.
Rn
Rn
Rn
R1
..
.

Since also det(Ea,b (r)) = 1, we have det(Ea,b (r)A) = det(A) = det(Ea,b (r)) det(A).
Let

R1
..
.

Ra
.

A = det
.. .
R
b
.
..
Rn

R1
R1
..
..
.
.

Rb

 Ra
.

a b
1

.
det(Sa,b A) = det
.. = sgn b a .. = (1) det(A) = det(A).
R
R
a
b
.
.
.
.
..
Rn
Rn
On the other hand, we also have det(Sa,b ) = 1. So det(Sa,b A) = det(A) =
det(Sa,b ) det(A).

R1
R1
..
..
.
.

det(Ta (r)A) = det rRa = r det Ra = r det(A) = det(Ta (r)) det(A).
.
.
..
..
Rn
Rn
All the above give us det(EA) = det(E) det(A) whenever E is an elementary matrix.

(2.15) We

2
1
A=
2
0

## do this exercise in the express way.

2 3
0
0 2 2
0
0 0 8 4
E3,2 (2)E1,3 (1) 1 1
E2,4 (1)E3,4 (2)E1,4 (2) 1 0
1 3 1
3 1
6 3

0 1 0
0 2 5 2
0 0 11 6
1 3 2
0 1 3 2
0 1 3 2

1 0 6 3
1 0 6 3
E4,3 ( 118 ) 0 1 3 2
S2,4 S1,2 0
1
3
2

0 0 11 6 0 0 11 6 = B
4
0 0 8 4
0 0 0
11
From the calculation above, we see that det(A) = det(B) = 4.
(2.17) If A is invertible, let B be its inverse, then AB = In . Taking determinant, we have
det(A) det(B) = det(AB) = det(In ) = 1. Thus det(A) 6= 0.
Conversely, suppose that det(A) 6= 0. Let R be the reduced row echelon form of A. Thus
EA = R for some E as a product of elementary matrices. If R has a row of zero entries then
det(R) = 0 and we get det(E) det(A) = det(R) = 0. But det(E) = det(E1 ) det(Ek ) 6= 0.
So det(A) = 0. This contradicts to our original assumption that det(A) 6= 0. Thus R cannot
have a row of zero entries. Since R is also a square matrix, we must have R = In and hence
EA = In . This shows that A is invertible whose inverse is E.
(2.19 (iii)) The equations
Ea,b (r)> = Eb,a (r)
Sa,b > = Sb,a
Ta (r)> = Ta (r)
are easy to obtain. The determinant of an elementary matrix E depends only on the form
of E whether it is E , S or T . After taking transpose of E, we have seen that its form
doesnt change (E remains E and so on). Thus we must get det(E > ) = det(E).
(2.27) Expand along certain row or column with the most number of zero entries. In this example,
we choose the fourth column.

2 2 3
0
2 2 3
2 2 3
1 1 3 1
2+4
4+4

det
2 0 1 0 =(1)(1) det 2 0 1 + 2(1) det 1 1 3
0 1 3
2 0 1
0 1 3 2





0 1
2 3
1+1
2+1
= 2(1) det
+ 2(1) det
(along first column)
1 3
1 3





2 3
2 2
3+1
3+3
+ 2 2(1) det
+ (1)(1) det
(along third row)
1 3
1 1
= ((2) 1 2 (9)) + 2 (2 3 1 0)
= 4.




1 2
1 2
2+3
3+3
(2.32) det(A) = 1 (1) det
+ 3(1)
= 9. The (i, j)-entry of adj(A) is
1 2
1 1
A(j,i) . These can be easily computed. Once you have obtained A1 , it is a good habit
to check that you actually get AA1 = In .